Acute effects of a single bout of high-intensity strength and endurance exercise on cognitive biomarkers in young adults and elderly men: a within-subjects crossover study - Bekkos, Carolin Haberstroh; Sujan, Md Abu Jafar; Stunes, Astrid Kamilla; Tari, Atefe Rafiee; Aagård, Norun; Brobakken, Cathrine Langlie; Brevig, Martin Siksjø; Syversen, Unni; Wang, Eivind; Mosti, Mats Peder (Journal of translational medicine, 2025)
Background Although evidence for exercise-induced changes in neurocognitive biomarkers is emerging, research examining acute responses to different exercise regimes across sex and age is lacking. This study investigated serum concentrations of three neurocognitive biomarkers (i.e., Klotho, brain-derived neurotrophic factor (BDNF), and glycosylphosphatidylinositol-specific phospholipase D1 (GPLD1)) after acute strength and aerobic exercise, along with skeletal muscle gene expression. Methods In a within-subjects crossover design, blood samples of 19 young women, 20 young men, and 14 elderly men were taken before, immediately, 3 h and 24 h after one bout of strength training (ST) and high-intensity interval training (HIIT). Muscle biopsies were taken from a subgroup (n = 22) before, 3 h and 24 h after ST and HIIT for gene expression analyses. Time changes and baseline levels, including the influence of sex and age, were analyzed using a multilevel model and Welch’s analysis of variance, respectively. Biomarker levels were adjusted for exercise-induced plasma volume changes. Results Serum concentration of all biomarkers increased after ST and HIIT but were not affected by sex or age. While serum Klotho and BDNF levels peaked immediately after exercise in all groups, serum GPLD1 levels were highest at 3 h (young groups only). Age was a determining factor for baseline measures; young men had higher and lower resting serum Klotho and BDNF concentration, respectively, than elderly men. Muscle gene expression of Klotho increased after both exercise modes, and BDNF and GPLD1 expression was reduced within 24 h. Conclusions Circulating levels of biomarkers linked to brain health can acutely be increased by one bout of ST or HIIT. This increase might be related to altered gene expression of these proteins in skeletal muscle. Ultimately, this could have beneficial implications for the management of mental and neurocognitive impairments.